PREVALENSI MASALAH MENTAL EMOSIONAL REMAJA DI KOTA PEKANBARU - Devita, Yeni (Universitas Prima Indonesia, 2019)
Mental problems emotional circumstances in which it identifies an individual experiencing an emotional change so that it can develop into a pathological condition if it continues, so that should be anticipated so that sanity is maintained (Kusuma, 2014). The results of the WHO study found 1 in 5 children aged less than 16 years of experience mental emotional problems. Basic Health Research (Riskesdas) in 2013 shows the prevalence of mental disorders in people emotionally Indonesia with age above 15 years is 6.0%. Health Data Survey Indonesia (IDHS, 2012) reported adolescents aged 15-19 years have shown aberrant behavior and emotional problems .This study aimed to determine the prevalence of adolescent mental emotional problems. Descriptive study design, sample of 266 adolescents with cluster sampling. Research was conducted at Kelurahan Tuah Karya Kecamatan Tampan, Riau Province. The results of the study show that mental problems emotional teenagers included in the category of borderline with the average of 18.45. The mean age of 16.63 years old teenager. Teen sex 45.1% male and 54.9% female. Youth education 82% higher education and 18% low education. Socioeconomic level 58.3% lower and 41.7% higher. Suggestions to further develop the scientific spirit of nursing education-related mental problems emotional teenagers to prevent deviant behavior in adolescents.